Adab Raja-Raja - Mohd. Taib Osman, 1934- (Perpustakaan Negara Malaysia : Kementerian Kebudayaan, Kesenian dan Warisan Malaysia, 2006)
History and criticism of Adab Raja-Raja, a classical Malay literature regarding Malay kings, nobles, and Islamic ethics.